A randomized, open-label pilot of the combination of low-level laser therapy and lorcaserin for weight loss. Issue 1 (December 2016) - Croghan, Ivana; Ebbert, Jon; Schroeder, Darrell; Hurt, Ryan; Hagstrom, Victoria; Clark, Matthew
Abstract Background Obesity is a significant public health problem and innovative treatments are needed. The purpose of this pilot study was to assess the preliminary efficacy and safety of a combined treatment of low-level laser therapy (LLLT) and lorcaserin on weight loss, health quality of life (QOL) measures, and cardiovascular risk factors. Methods Forty-five overweight and obese adult participants with a body mass index (BMI) >26.9 and <40 were randomized to receive LLLT, lorcaserin, or a combination of the two therapies. All study participants received treatment for 3 months and were followed for 3 months post-treatment. Participants were recruited from June 2014 through September 2014. Results The majority of the 44 participants accrued to this study were female (84 %) with an average age of 43.9 years (range 22 to 64 years). Most participants (93 % LLLT alone, 87 % LLLT + lorcaserin) completed at least 80 % of the LLLT treatments. From baseline to end of treatment, significant reductions in waist circumference were noted for each treatment group (-2.3 ± 4.1 cm, -6.0 ± 7.3 cm, and -4.0 ± 5.5 cm for LLLT, lorcaserin and combination respectively); however, the reduction in body weight was only significant in those receiving lorcaserin and combination treatment (-0.4 ± 1.5 kg, -1.3 ± 1.2 kg and -1.3 ± 1.3 kg). No significant differences were noted between the groups. Self-reported satisfaction was higher in the lorcaserin versus the LLLT group. Conclusion This small pilot demonstrates that when combined with behavioral intervention, Lorcaserin and LLLT may be effective components of a comprehensive approach to the treatment of overweight and obesity in the clinical setting. Further studies with larger sample size and longer duration of treatment and follow-up are needed to further address efficacy. Trial Registry Information Trial registration:NCT02129608 . Registered June 15, 2014.